Dexmedetomidine suppresses microglial activation in postoperative cognitive dysfunction via the mmu-miRNA-125/TRAF6 signaling axis - Xu Zhiyan; Zhong Kaihua; Chen Weiyuan; Lan Huixia; Zhong Weifeng; Wang XiaoHong; Chen Mu; Pan Bin (Open Medicine, 2025)
Postoperative cognitive dysfunction (POCD) is driven in part by microglial activation and the resulting neuroinflammatory response. Emerging evidence suggests that microRNAs regulate key inflammatory pathways in the central nervous system. In this study, we examined the role of the mmu‑miR‑125a/TRAF6 signaling axis in microglial activation under inflammatory conditions induced by lipopolysaccharide (LPS) and surgical trauma and evaluated whether dexmedetomidine (DEX) modulates this pathway to alleviate POCD.